Accounting policies, institutional factors and firm performance: Qualitative insights in a developing country - Daniel Badulescu; Muhammad Nouman Akhtar; Mumtaz Ahmad; Mariam Abbas Soharwardi (Journal of Risk and Financial Management, 2021)
This study aims to uncover the determinants for the formulation of accounting practices and their impact on firm performance in Pakistan through the lens of institutional theory. Based on a pragmatic approach, this study has collected data from 455 participants and 21 semi-structured interviews have been conducted. Firstly, it is noted that accounting practices can be traced back to the Mughal regime, and subsequently underwent a major development in the British colonial system. Secondly, our results indicate that institutional factors, namely, accounting regulatory framework, political factors, economic factors, cultural factors, and country-specific factors have also played a major role in the development of accounting practices after the creation of Pakistan as a separate state. Finally, this study suggests that the development of accounting practices have a novel contribution towards the performance of firms. This research thus provides a pathway for policymakers in this county to closing the gaps between accounting practices and the policies of the International Accounting Standard Board (IASB). Furthermore, firms can enhance their performance by implementing international accounting standards. This paper helps Pakistan's regulatory institutions such as the SECP (Securities and Exchange Commission of Pakistan) and SBP (State Bank of Pakistan) in the process of developing new policies. Such decisions are related, but not limited to: attracting foreign investments, economic expansion, and international trade. Furthermore, it provides a pathway for firms to improve their performance. Ultimately, this research fills the gap as concerns international accounting standards by assessing, both empirically and theoretically, the role of various determinants for the formulation of accounting practices and their impact on the performance of firms.
Keywords: 330; accounting practices; companies financial performance; developing country; institutional factors; Pakistan